Scope and Exercise of the Exclusive Competences of the Member States of the European Union - Krzysztofik, Edyta Anna (Review of European and Comparative Law, 2020)
The process of European integration has introduced the Member States into a new legal reality. The existing exclusivity in the area of competence implementation has been replaced by a two-stage model of their exercise. The Member States, when conferring part of their supervisory powers, did not specify the scope of their own competences. The so-called European clauses were analysed in the Constitutions of selected Member States, which showed that they define the recipient of the conferral and, in a non-uniform manner, specify the subject of the conferral. The analysis of the indicated provisions clearly shows that the Constitutions of the Member States exclude full conferral of competences on the European Union. There is no specification of the scope of competences that may be conferred. However, this issue was addressed by Constitutional Courts of the Member States. The article refers to the judgements of the German Federal Constitutional Court and the Polish Constitutional Court. It has been shown that they equate exclusive competences of the Member States with the scope of the concept of constitutional identity reduced to basic principles of the state. The Court of Justice of the European Union analysed the scope of competences of both entities. The article presents the analysis of judgements on: entries in Civil Registry regarding transcription of surnames, the issue of recognition of same-sex marriages, reform of the judiciary system in Poland, and the application of the Charter of Fundamental Rights in the areas that do not fall under EU competence. Regardless of the division of competences, the EU is bound by the principle of respect for national identity of the Member States, including constitutional identity. It both obligates the EU to respect the exclusive competences of the Member States and is a premise restricting the achievement of EU objectives.